AN ASSESSMENT OF THE ROLE OF ISE IN DA’WAH ACTIVITIES IN EGGONLAND - Sule, Mohammed Maga (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2022)
This paper documents and also assess the different method employed by ISE for its Da’wah Activities in Eggonland. The study highlight the Da’wah approaches and methodology of Islamic Society of Eggonland and its contributions. The study also found that the coming of ISE with modern Da’wah train, a different Da’wah to proselytize Islam and its beauty to people of Eggonland and the wider world through its various humanitarian programmes that are geared towards building the Ummah is yielding result. It is a successful of because in its humanitarian programme people are equally treated irrespective of their religion. The study adopted Survey method using primary sources, where interview and observation were to obtain data on the Da’wah activities of the ISE. This research is expected to become a model for the development of Da’wah in a multi-religious society. The findings are essential for Islamic Da’wah organizations to redesign and formulate various modern Da’wah programmes in order to ensure improved way to engage the people.